Teachers' Perspectives on Task-Based Language Teaching: Practices, Strengths, and Weaknesses - Bhandari , Bhimlal (SNPRC Journal, 2024)
Task-Based Language Teaching (TBLT) as a modern, effective and widely discussed method prioritizes purposeful tasks to improve students' communicative competence. Although it enhances classroom engagement through authentic language use, the majority of English teachers in Nepal continue to employ conventional methods, with very few embracing learner-centred, task-based practices. This study explores teachers' perspectives on task-based language teaching: practices, strengths, and weaknesses. It employs a narrative research design to explore participants' lived experiences of TBLT. Four secondary school teachers from Rupandehi, Nepal were purposefully chosen. Information was collected through semi-structured interviews. The raw data was transcribed and translated into English, coded, organized it into themes, analyzed and interpreted descriptively to derive meaning. This study reveals that teachers hold positive perceptions of TBLT that can improve students’ communication, critical thinking, and problem-solving skills. It also encourages learners' freedom and integrates linguistic skills. However, exam-focused curricula, resource constraints, students' unwillingness to collaborate and insufficient teacher training are challenges in its implications. The study can contribute to teachers adopting the learner-centered approach in their classrooms.